Infant temperament and parent use of food to soothe predict change in weight-for-length across infancy: early risk factors for childhood obesity - Stifter, Cynthia A.; Moding, Kameron J. (International Journal of Obesity, 2018)
Objectives Greater weight gain in infancy is a risk factor for childhood obesity. The present study examined the interaction between infant temperament and parent use of food to soothe infant distress (FTS) as predictors of weight gain across the first 2 years of life. Subjects/Methods A total of 160 mother–infant dyads were recruited into a longitudinal study. Infant temperament was assessed by parents through a questionnaire (surgency, negativity) and by observer ratings (surgency, irritability) during a laboratory visit when infants were 6 months old. Parents also completed a 3-day infant cry diary when their children were 6 months of age to assess when they used food in response to infant cry/fuss bouts. Infant weight/length was measured in the lab at 6 and 18 months. Multiple regressions were run to test the moderating effect of FTS on weight gain. Results Significant interactions were revealed for both measures of surgency and parent FTS in predicting weight gain. Surgent infants whose parents had a greater tendency to use FTS had greater weight-for-length gain in 1 year than if their parents tended to use less FTS. The interaction between observer ratings of irritability and parent FTS was also significant but in an unexpected direction. Conclusions The findings point to the role of temperament, specifically surgency, in weight gain during infancy, but only if their parents used FTS. Surgency may have evoked this feeding practice that increased their health risk.